Chicken homolog of the mos proto-oncogene. - Schmidt, M (1988)
We compared the sequence and properties of the chicken mos homolog with the previously characterized mouse and human c-mos genes. Sequence analysis revealed one major open reading frame of 1,047 base pairs encoding a protein of 349 amino acids. Both the nucleotide sequence and the deduced amino acid sequence showed 62% overall homology to mouse and human c-mos, but regions of higher conservation (approximately 70%) occurred in the putative ATP-binding and kinase domains. We detected mos transcripts by Northern (RNA) analyses in RNA prepared from chicken and quail ovaries and testes. Evidence for low levels of mos RNA expression in adult chicken heart, kidney, and spleen and in the entire embryo was obtained by S1 nuclease protection experiments. In contrast to the low transforming efficiency of human c-mos when linked to a mouse retroviral long terminal repeat element, chicken c-mos transformed NIH 3T3 cells as efficiently as mouse c-mos did. We also show that chicken primary embryo fibroblasts were morphologically altered when infected with an avian retroviral vector containing the chicken c-mos coding region.